2017
DOI: 10.17844/jphpi.v20i1.16498
|View full text |Cite
|
Sign up to set email alerts
|

Production of Alginate Oligosaccharides (AOS) as Prebiotic Ingredients through by Alginate lyase enzyme

Abstract: AbstrakPrebiotik merupakan bahan makanan yang tidak dapat dicerna tetapi dapat menstimulasi pertumbuhan dan aktivitas bakteri di dalam sistem pencernaan. Alginate oligosaccharides (AOS) dapat digunakan sebagai sumber prebiotik. Senyawa tersebut dapat dihasilkan secara enzimatis dengan memotong rantai panjang alginat menggunakan alginat liase. Penelitian ini bertujuan untuk menghasilkan enzim alginat liase yang digunakan untuk memproduksi AOS sebagai bahan prebiotik. Enzim alginat liase dapat dihasilkan dari ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
3
2
0
1
Order By: Relevance
“…With glucose, bacteria can convert carbon into biohydrogen. This aligns with the findings of Afni et al (2017), stating that alginate has a long polymer structure, which takes a considerable amount of time in the polymer degradation process for bacteria to digest. Moreover, it is also influenced by the chemical structure of alginate, which consists of mannuronate and guluronate with different properties.…”
Section: Discussionsupporting
confidence: 91%
“…With glucose, bacteria can convert carbon into biohydrogen. This aligns with the findings of Afni et al (2017), stating that alginate has a long polymer structure, which takes a considerable amount of time in the polymer degradation process for bacteria to digest. Moreover, it is also influenced by the chemical structure of alginate, which consists of mannuronate and guluronate with different properties.…”
Section: Discussionsupporting
confidence: 91%
“…However, banana corm extract has a degree of polymerization (DP) of 2.54 (Table 1) which means it qualifies to be a source of prebiotics. This is following the opinion of Afni et al, (2017) that oligosaccharides with DP 2-5 can be used as prebiotics. Furthermore, Nuraida et al (2011) stated that a low DP value would be easier for lactic acid bacteria to ferment in support of their growth.…”
Section: Extraction and Fractionation Resultssupporting
confidence: 53%
“…Thin Layer Chromatography (TLC) and Fourier Transform Infra-Red Spectroscopy has been clearly defined that alginate from Sargassum siliquosum which also applied in this present research, is characterized by mannuronate and guluronate monosaccharide (Yudiati et al, 2017;Yudiati et al, 2016). Based on the results, this present study revealed that alginate monosaccharide was degraded and digested by probiotic bacteria, strengthened to research by Afni et al, (2017), using AOS from brown seaweed Sargassum crassifolium.…”
Section: Prebiotic Test Of Alginate Polysaccharides and Aossupporting
confidence: 67%
“…Moreover, synbiotics have also been revealed to substitute and solve the antibiotic-resistant negative effects (Su et al, 2011). Besides, the combination prebiotics application could enhance the higher promotion of immune response and growth parameters of aquatic species (Li et al, 2018) Afni et al, (2017 reported AOS produced enzymatically as prebiotics on shrimp culture. Even though, up to now, there is still limited information concerning alginate oligosaccharide as prebiotic for probiotic bacteria.…”
Section: Probioticmentioning
confidence: 99%